2014
DOI: 10.1177/1071100714550647
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study of Chevron Osteotomy Versus Mitchell’s Osteotomy in Hallux Valgus

Abstract: Level I, prospective randomized study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
13
0
2
Order By: Relevance
“…The rate of transfer metatarsalgia was probably underreported due to incomplete documentation (8,9). The rate of 11.6% undercorrection found in the present study corresponds with rates reported, albeit with varying definitions and periods of followup, in the literature.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The rate of transfer metatarsalgia was probably underreported due to incomplete documentation (8,9). The rate of 11.6% undercorrection found in the present study corresponds with rates reported, albeit with varying definitions and periods of followup, in the literature.…”
supporting
confidence: 83%
“…The corrections of IMA were a little better than those quoted in literature, 6.1 versus the mean of 5.3 degrees by the review of Smith et al (7) Other results of angular correction were similar to those reported in the recent literature. (6,8,14,15,25) However, limited patient numbers, different measurement methods, and divergent indications for the chevron complicate direct comparisons between those studies and our project. Another limitation is the amount of loss-to-follow up leading to a final response rate of those who filled in the FAOS of 60%.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, by Buciuto, 120 patients were randomized to either chevron osteotomy or Mitchell osteotomy treatment groups 35 . The authors found that patients in the chevron osteotomy group had significantly higher AOFAS scores, fewer postoperative complications (e.g., transfer metatarsalgia), higher patient satisfaction, and fewer missed work days compared with the Mitchell osteotomy group.…”
Section: Hallux Valgusmentioning
confidence: 99%
“…The shortening, dorsiflexion, and elevation of the first metatarsal, which shift the first metatarsal head toward a more dorsal position, thereby transferring weight to the second metatarsal, have been recognized by many foot surgeons as a cause of metatarsalgia and poor surgical results. 5,6,32 The metatarsalgia caused by the elevation of the first metatarsal head had been reported to be one of the most frequent complications in DLMO or similar minimally invasive distal metatarsal osteotomies. 19,45 In the present research, postoperative metatarsalgia occurred in 10.0%, although the rate is not high compared with other procedures, 5,17 and the clinical outcome during the short follow-up period was acceptable.…”
Section: Discussionmentioning
confidence: 99%